Выражение 1) (5+b)(b-5)-b^2 2)c^2+(9-c)(9+c) 3)(1/3-z)(1/3+z)-1/9. 4)-16/49+(4/7-d)(d+4/7) 5)(0,9-a)(a+0,9)-a(1+a) 6)k(5-k)+(1,2+k)(k-1,2)

MadalinaT MadalinaT    2   05.10.2019 04:00    0

Ответы
marina2770 marina2770  09.10.2020 20:59

1)  (5+b)(b-5)-b²=(b+5)(b-5)-b²=b²-25-b²=-25

2) 2) c²+(9-c)(9+c)=c²+81-c²=81

3) 3) (1/3-z)(1/3+z)-1/9=1/9-z²-1/9=-z²

4)  4)-16/49+(4/7-d)(d+4/7)=-16/49+(4/7-d)(4/7+d)=-16/49+16/49-d²=-d²

5) 5)(0,9-a)(a+0,9)-a(1+a)=(0,9-a)(0,9+a)-a-a²=0,81-a²-a-a²=               =   -2a²-a+0,81

      6)k(5-k)+(1,2+k)(k-1.2)=-k²+5k+(k+1.2)(k-1.2)=-k²+5k+k²-1,44=5k-1,44

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра